1971
DOI: 10.1099/00221287-67-2-215
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Spores of Clostridium bifermentans by Certain Amino Acids, Lactate and Pyruvate in the Presence of Sodium or Potassium Ions

Abstract: Spores of Clostridium bifermentans germinated in the presence of L-alanine and sodium ions. The rate of germination was not altered by the addition of D-alanine but was increased by L-a-amino-n-butyrate, L-lactate, L-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1974
1974
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 11 publications
3
20
1
Order By: Relevance
“…The strain of Clostridium b fermentans used and the preparation and storage of spores were as described previously (Waites & Wyatt, 1971) except that spores were produced on a trypticase agar containing (g 1-l): Trypticase (BBL), 30 ; yeast extract (Difco), I '0 ; ammonium sulphate, 10 ; agar, I 2 ; adjusted to pH 7-3 with I M-NaOH. The organism was maintained in the reinforced clostridial medium of Hirsch & Grinsted (1954).…”
Section: Methodsmentioning
confidence: 99%
“…The strain of Clostridium b fermentans used and the preparation and storage of spores were as described previously (Waites & Wyatt, 1971) except that spores were produced on a trypticase agar containing (g 1-l): Trypticase (BBL), 30 ; yeast extract (Difco), I '0 ; ammonium sulphate, 10 ; agar, I 2 ; adjusted to pH 7-3 with I M-NaOH. The organism was maintained in the reinforced clostridial medium of Hirsch & Grinsted (1954).…”
Section: Methodsmentioning
confidence: 99%
“…The strain of Clostridium byermentans used and the preparation and storage of spores have been described previously (Waites & Wyatt, 1971).The organism was maintained in the reinforced clostridial medium of Hirsch & Grinstead (1954).…”
Section: Methodsmentioning
confidence: 99%
“…No comparable data are available for clostridia. Spores of Clostridium bij2rmentans germinate with sodium ions and either L-alanine or various mixtures of other amino acids (Waites & Wyatt, 1971). This paper reports the effect of conditions on the germination of C .…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that spores of C. bifermentans germinate in the presence of L-alanine, L-arginine, L-phenylalanine, and L-lactate, even though no Ger receptor has been identified in this species (Waites and Wyatt, 1971). This is similar to our recent findings that showed that C. sordellii, a close relative of C. bifermentans, needs a combination of a small amino acid, a basic amino acid, an aromatic amino acid, and bicarbonate to germinate (Ramirez and Abel-Santos, 2010).…”
Section: Germination Response In Clostridium Bifermentans and Clostrimentioning
confidence: 97%